FLEKSIBILITAS TRADISI PESANTREN TERHADAP KEKERASAN PADA ISTERI (STUDI KASUS PADA PENERAPAN UU PKDRT DI LINGKUNGAN PESANTREN KAB. JOMBANG) - Hyma Puspytasari, Heppy (Jurnal Pendidikan Kewarganegaraan Undiksha, 2021)
The pesantren community has actually been aware of the issue of domestic violence (KDRT) for a long time, but that does not mean they really understand the meaning of domestic violence as a whole. Because in reality, domestic violence itself is hidden in the world of pesantren households. Other things that may also be the cause of the occurrence of domestic violence in the pesantren are the kyai's patrons as leaders of the pesantren who cannot be shaken by anything. Many facts also support that the words of the kyai are always true and never wrong, because he is considered the most understanding of religious teachings. Apart from that, the existence of a verse which states about the nusyus of a wife, and the family study which says "may hit" is taken literally. The special condition of the traditions in the pesantren and the controversy between the traditions in the pesantren and the PKDRT Law makes this interesting to be investigated further. The purpose of this research is to find out: Does the pesantren tradition trigger domestic violence and how to overcome domestic violence in pesantren? The approach used in this research is the socio legal research approach, namely through this approach the law is also conceptualized as an empirical social phenomenon, namely in the daily actions and interactions of citizens, not only as laws or judges' decisions. The results of this study indicate that the pesantren tradition does not trigger domestic violence even though it is possible that there is gender imbalance in husband and wife relationships, but traditions in pesantren provide more learning that supports emancipation and gender equality without leaving religious norms. Whereas alternative solutions for handling domestic violence in pesantren were not held because there were no incidents that referred to domestic violence, but to prevent domestic violence, pesantren also contributed roles through the educational approach for santri, namely education on fair husband and wife relationships and acknowledging equality but still within the frame. the teachings of the Islamic religion, according to each other's nature by still helping each other in all parts of the household. Keywords: Islamic boarding school tradition, domestic violence